University lecturers’ perceptions of Padlet and its impact on classroom practices - Yunos, Farah Naaz Abd; Singh, Gurdip Kaur Saminder; Kumar, Menaga; Hanefar, Shamsiah Banu Mohamad; Naidu, Sumitra Ravindran (International Journal of Innovative Research and Scientific Studies, 2025)
This study delves into university lecturers’ perceptions of Padlet as an educational tool, emphasizing its ease of use, usefulness, and impact on teaching productivity. Conducted as a qualitative case study, data were gathered through in-depth, semi-structured interviews with lecturers selected through purposive sampling, to ensure participants met predefined criteria of having Padlet experience, thereby enhancing the relevance and richness of the data collected. Thematic analysis, following Braun and Clarke’s framework, revealed five key themes: lecturers’ familiarity and impressions of ease of use, perceived usefulness and functionality, integration of Padlet into teaching practices, Padlet as a classroom management tool, and perceived impact on teaching practices. Overall, the study highlights Padlet’s potential as a powerful educational tool, particularly in supporting blended learning environments in higher education. Findings of this study provide insights for educators and institutions seeking to promote the effective integration of digital tools into teaching and learning, especially in the context of higher education.